How do Germans react to the commuting allowance? - Martin Weiss (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
I research the consequences of changes in the deductibility of commuting costs in Germany from 2001 to 2006. Official figures provided by the Federal Statistical Office highlight the fact that German taxpayers claimed deductions for commuting allowances to the tune of 23-29 billion e over the years 2001-2004. Granting or not granting these deductions thus has wide ranging fiscal implications, a point made more poignant by the fact that Anglo-Saxon countries have never allowed them. To determine whether Germans do react to the commuting allowance, I exploit the variation in the amount per kilometer granted between fiscal years 2003 and 2004 by looking at taxpayers featuring sufficient labor earnings and longish commuting distances whose deductions unambiguously exceed the basic allowance in the German Income Tax Code. I try to find evidence of changes along several behavioral margins in response to variations in the deduction granted. Labor supply behavior turns out to be unresponsive while the commuting distances do show a palpable reaction.
Keywords: 330